(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
The purpose of this article is to analyze how Foucault’s interest in spaces was related to historical problematization about the notion of life. Contrary to a dichotomous look between time and space, Foucault’s intellectual path has privileged a historical perspective that was spatially configured. From two different moments of the archaeogenealogical period, between the 1960s and 1970s, the article seeks to verify how Foucault intertwined history, spaces and life, and how these reflections are articulated with historiography